Biophysical characterization of drug‐resistant mutants of fibroblast growth factor receptor 1. (25th August 2016) - Yoza, Kaito; Himeno, Rika; Amano, Shinjiro; Kobashigawa, Yoshihiro; Amemiya, Shun; Fukuda, Natsuki; Kumeta, Hiroyuki; Morioka, Hiroshi; Inagaki, Fuyuhiko
Abstract : Over‐expression and aberrant activation of tyrosine kinases occur frequently in human cancers. Various tyrosine kinase inhibitors (TKIs) are under clinical use, but acquisition of resistance to these drugs is a major problem. Here, we studied the interaction between two drug‐resistant mutants of fibroblast growth factor receptor 1 (FGFR1), N546K and V561M, and four ATP‐competitive inhibitors, ponatinib, dovitinib, PD173074 and BGJ‐398. Among these protein–drug systems, the only marked reduction in affinity was that of PD173074 for the V561M mutant. We also examined the interaction of these FGFR1 variants to AMP‐PNP, a nonhydrolyzable analogue of ATP, and showed that N546K showed increased affinity for the ATP analogue as compared with the wild type. These findings will help to clarify the mechanism of drug resistance in mutant tyrosine kinases. Abstract : Affinity of drug‐resistant mutants of FGFR1 for ATP‐competitive inhibitors were evaluated by biophysical techniques. The only marked reduction in affinity was observed that of PD173074 for the gatekeeper mutant (V561M). The molecular brake mutant (N546K) exhibited increased affinity for the ATP‐analogue. These findings will help to clarify the mechanism of drug‐resistance in mutant tyrosine kinases.